Rapid refeeding does not worsen anxiety in adolescents with anorexia nervosa: a pilot study. Issue 6 (2nd November 2022) - Akgül, Sinem; Bonny, Andrea E; Manos, Brittny E.; Jackson, Kenneth; Holland-Hall, Cynthia
ABSTRACT: The study aimed to describe the progression of state anxiety in adolescents with anorexia nervosa (AN) hospitalized on a high calorie refeeding (HCR) protocol. Participants, 12–21 years, admitted for malnutrition due to AN were placed on a HCR protocol in which calories were advanced by 300 kcal/day. The State-Trait Anxiety Inventory for Children (STAIC) was given to participants within 24 hours of hospitalization and the state anxiety component of the STAIC was administered daily immediately before and after breakfast until discharge. Of 22 patients enrolled, 86% were female, mean age was 14.9 ± 2.0 years, and 95% had AN-restrictive type. The median state and trait anxiety scores at time of admission were 37.0 (28–55) and 35.5 (23–51), respectively. There was no significant difference in median pre-meal state anxiety from hospital day 1 to 6 (34.0(26–55) vs. 38.5(25–55), p -value = 0.079) or in median post-meal state anxiety from hospital day 1 to 6 (35.5(29–56) vs. 37(24–56), p -value = 0.484). Similarly, we found minimal correlation between change in caloric intake and change in pre-meal S-anxiety (Spearman correlation coefficient = −0.032) or post-meal S-anxiety (Spearman correlation = 0.032). While this was a small sample observing anxiety over one week, we found no evidence that state anxiety increased with advancing calories, providing additional support for the use of more rapid refeeding protocols.